2019
DOI: 10.1289/ehp2854
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Residential Greenness as a Predictor of Cause-Specific Mortality and Stroke Incidence in the Rome Longitudinal Study

Abstract: Background:Living in areas with higher levels of surrounding greenness and access to urban green areas have been associated with beneficial health outcomes. Some studies suggested a beneficial influence on mortality, but the evidence is still controversial.Objectives:We used longitudinal data from a large cohort to estimate associations of two measures of residential greenness exposure with cause-specific mortality and stroke incidence.Methods:We studied a population-based cohort of 1,263,721 residents in Rome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 43 publications
4
48
1
Order By: Relevance
“…For NDVI, we considered a single satellite image taken at a single day in July. Although we did not account for the potential temporal variation in greenness, a previous study conducted in Rome showed negligible changes in the quantity of greenness during the study period [40]. Neither of the chosen indicators allowed us to distinguish between different types of vegetation, vegetation volumes, and types of green space (street trees or gardens).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For NDVI, we considered a single satellite image taken at a single day in July. Although we did not account for the potential temporal variation in greenness, a previous study conducted in Rome showed negligible changes in the quantity of greenness during the study period [40]. Neither of the chosen indicators allowed us to distinguish between different types of vegetation, vegetation volumes, and types of green space (street trees or gardens).…”
Section: Discussionmentioning
confidence: 99%
“…NDVI ranges from −1 to 1 (with higher numbers indicating more greenness) is based on land surface reflectance of visible (red) and near infrared radiation [33,36,37,38,39]. We downloaded a Landsat 8-OLI/TIRS remote sensing image of NDVI from the USGS database (), with a spatial resolution of 30 m × 30 m (Figure 1C), for the 17/07/2015, assuming this image was representative of the overall follow-up period exposure [40]. We were confident that this assumption could not bias our greenness indicator since Orioli et al demonstrated that the correlations between NDVI summer values across the period from 2001 to 2013 plus 2015 were always very high (about 0.80), denoting no substantially changes in the amount of greenness in the city of Rome [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating data indicate that a higher amount of neighborhood vegetation (referred to as residential greenness) is associated with a range of beneficial health outcomes. 3 , 4 A large number of studies have examined the cardiovascular associations of greenness, 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 but more than 50% of those focused on CVD mortality. In addition, most of the previous studies were conducted in middle- and high-income countries, and only a few studies were performed in low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…The association between greenspace and mortality risk has been identified by studies done in Australia, Canada, China, France, Italy (Rome), Japan, Korea, the Netherlands, the UK, and the USA. [3][4][5][6][7][8][9][10][11][12] Studies in these areas, however, have focused mainly on the effects of greenness per se. Few studies have investigated greenspace morphologyrelated metrics in predicting mortality.…”
Section: Introductionmentioning
confidence: 99%